Differences in playing style and technical performance according to the team ranking in the Spanish football LaLiga. A thirteen seasons study - González-Rodenas, J.; Ferrandis, J.; Moreno-Pérez, V.; López-Del Campo, R.; Resta, R.; Del Coso, J. (PLOS ONE, 2023)
This study aimed to explore the differences in playing style and technical performance according to the ranking level in Spanish football teams. The sample comprised 38 professional teams that competed in LaLiga from 2008/09 to 2020/21, with a total of 4940 matches. The teams were grouped by their final ranking position: Champion (1st); Champions League (2nd-4th); Europa League (5th-6th); middle teams (7th-17th); and relegated teams (18th-20th). Linear mixed models were used to examine the effects of the team ranking on variables related to playing style and technical performance. The F2 statistic was calculated as effect size (ES). Regarding the style of play, the Champion teams initiated offensive sequences from a more advanced field position than the remaining ranking groups with a descending effect as the ranking position decreased (p < 0.001; ES = medium). The sequence duration and passes per sequence showed a decreasing effect across ranking groups (both p < 0.001; ES = small). In contrast, the direct speed showed an increasing effect as the ranking position decreased (p < 0.001; ES = small). A decreasing effect was observed in the number of sequences ending in the final third as the ranking position decreased (p < 0.001; ES = large) while no effect was found for the sequences ending in a shot. There was a reduction effect in ball possession, passing accuracy, through balls and crosses as the teams` ranking decreased (all p < 0.001; ES = small-to-large). In summary, higher-ranked teams had an advanced starting position, longer offensive sequences, slower progression speed, more ball possession, higher passing accuracy, and more crosses and through balls than lower-ranked teams. Football coaches should consider that adopting a playing style focused on regaining the ball possession in advanced field zones and using long passing sequences can be an effective tactical strategy to improve the teams` ranking during the season.